Description of the karyotype of Tunisian Mayetiola hordei (Diptera: Cecidomyiidae) and comparison with M. destructor - BOUKTILA, DHIA; MEZGHANI, MAHA; MAKNI, MOHAMED; MAKNI, HANEM (Revista Colombiana de Entomología, 2009)
We report information about the structure of the karyotype of M. hordei, a fly that infests barley in the south of Tunisia. The number of chromosomes was found to be (2n = 8) in somatic female cells and (2n – 2 = 6) in somatic male cells, which is similar to the karyotype of M.destructor. Mitotic and polytene chromosomes of M. hordei are described and compared with those of M. destructor. The karyological data are discussed in terms of genetic mechanisms underlying divergence of M. hordei and M. destructor.